2021
DOI: 10.1021/acsanm.1c02092
|View full text |Cite
|
Sign up to set email alerts
|

Graphitic Carbon Nitride/Zeolitic Imidazolate Framework-8 Nanoparticles with Antibacterial Properties for Textile Coating

Abstract: Textiles that protect against bacterial nosocomial infections are vital owing to the associated high morbidity, mortality, and a series of challenges that remain in the treatment of drug-resistant bacteria. To overcome these hurdles, a universal coating was developed by combining g-C 3 N 4 /ZIF-8 heterojunction nanoparticles and hydrophobic waterborne polyurethane (PU) to form protective textiles with remarkable antibacterial, anti-adhesive, and antifouling performance. The g-C 3 N 4 /ZIF-8 nanoparticles produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…A perusal of the literature revealed that extensive research has been done regarding the use of ZnO in the textile industry due to its multifunctional properties such as antimicrobial activity, hydrophobicity, UV protection, and photocatalytic self-cleaning. Thus, based on the results of low toxicity and significant antibacterial potential as exhibited by the functionalized IL@ZnO, it is further anticipated that the functionalized IL@ZnO material may serve as a good coating material for textile substrates. A functional coating on a textile substrate enhances its performance and properties.…”
Section: Resultsmentioning
confidence: 99%
“…A perusal of the literature revealed that extensive research has been done regarding the use of ZnO in the textile industry due to its multifunctional properties such as antimicrobial activity, hydrophobicity, UV protection, and photocatalytic self-cleaning. Thus, based on the results of low toxicity and significant antibacterial potential as exhibited by the functionalized IL@ZnO, it is further anticipated that the functionalized IL@ZnO material may serve as a good coating material for textile substrates. A functional coating on a textile substrate enhances its performance and properties.…”
Section: Resultsmentioning
confidence: 99%
“…Mu et al (2021) synthesized g-C 3 N 4 /ZIF-8 heterojunction nanoparticles by an in situ method. 37 g-C 3 N 4 / ZIF-8 exhibited highly effective antibacterial efficacies of 91.1% and 95% against E. coli and S. aureus, respectively, after 30 min of light irradiation. This is because the synergistic combination of g-C 3 N 4 with MOFs would significantly improve the photocatalytic performance by augmenting the specific surface area and active reaction sites.…”
Section: In Vitro Researchmentioning
confidence: 99%
“…In addition, pure MOFs often suffer from rapid recombination of photogenerated electron-hole pairs, resulting in suboptimal photocatalytic performance. In order to solve the above problems and obtain better photocatalytic performance, functionalized MOF-based composites can be constructed by modifying pure MOFs, such as the decoration of linkers or metal centers, 35 metal nanoparticle (NP) doping, 36 construction of core-shell materials, 26 and bonding with semiconductors 37 and conductive materials. 38 These are very promising strategies to realize the visible light response of MOFs and enhance the photocatalytic performance of MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…Antibacterial agents are vital in the manufacture of antibacterial fibers, which is the base of the antibacterial textiles. The current antibacterial agents are mainly silver, copper, and other metal antibacterial agents, while they have many limitations, such as high cost, low biocompatibility, and poor comfort. Therefore, the selection of natural antibacterial agents with good biocompatibility and broad-spectrum durable antibacterial properties is the key to achieving a win–win situation between antibacterial and the comfort of antibacterial fibers. , …”
Section: Introductionmentioning
confidence: 99%